2018
DOI: 10.1089/apc.2018.0038
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Solutions to Improve the Sexually Transmitted Infections Testing Experience for Youth Through Participatory Ideation

Abstract: Sexually transmitted infection (STI) services, including screening, treatment, and counseling among youth, remain suboptimal. In the midst of increasing incidence of bacterial STIs, alarming STI disparities, and persistently low testing rates among youth, solution-focused and action-oriented research with youth is needed. To identify solutions to STI testing barriers, we conducted three participatory ideation workshops with 18 youth, 10 key stakeholders who work with youth, and 8 social design graduate student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[21][22][23] The reported rates of CT infection and gonorrhoea cases in adolescents in our setting are below the European average, 15,16 reflecting not only the lack of an opportunistic or systematic screening programme for CT but also the barriers faced by adolescents seeking medical care. 24 Further studies are needed to investigate this in our setting. Although these three STIs have been nationally notifiable conditions since 2007, the implementation of electronic medical reporting in 2011 and electronic integration of SNM and MDO systems in 2014 have improved the under-reporting of cases to Catalan Mandatory Notifiable System.…”
Section: Discussionmentioning
confidence: 97%
“…[21][22][23] The reported rates of CT infection and gonorrhoea cases in adolescents in our setting are below the European average, 15,16 reflecting not only the lack of an opportunistic or systematic screening programme for CT but also the barriers faced by adolescents seeking medical care. 24 Further studies are needed to investigate this in our setting. Although these three STIs have been nationally notifiable conditions since 2007, the implementation of electronic medical reporting in 2011 and electronic integration of SNM and MDO systems in 2014 have improved the under-reporting of cases to Catalan Mandatory Notifiable System.…”
Section: Discussionmentioning
confidence: 97%
“…[30][31][32][33] Participatory methods have been shown to effectively elucidate key issues around STIs that are pertinent to communities related to the planning of clinical STIs services delivery. 17,35,36 For example, a study in the United States adopted a series of participatory ideation workshops with youth and other key stakeholders in STIs services. 35 The researchers found that such an approach led to identifying themes beyond general barriers and motivators to STIs testing and included relevant solutions as well.…”
Section: Planning Clinical Stis Services Deliverymentioning
confidence: 99%
“…17,35,36 For example, a study in the United States adopted a series of participatory ideation workshops with youth and other key stakeholders in STIs services. 35 The researchers found that such an approach led to identifying themes beyond general barriers and motivators to STIs testing and included relevant solutions as well. The same team also adopted creative visual mapping approaches to better understand the youth's experiences in clinical STIs services uptake, which helped to identify issues and solutions informed by their lived experiences of utilising such clinical STIs services.…”
Section: Planning Clinical Stis Services Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recent research has aimed to increase rates of STI testing among youth. 2 However, to our knowledge, no national data exist to characterize STIs 3 in transgender and other gender minority youth (TGMY) who have a gender identity that differs from their sex assigned at birth. This is because TGMY are not routinely ''counted'' in STI surveillance systems using a methodology that allows for disaggregation of results by gender identity.…”
Section: Introductionmentioning
confidence: 99%